The effect of booklet-based education on vaginal discharge knowledge among women of childbearing age - Ana Mariza; Zera Androla; Susilawati Susilawati; Sunarsih Sunarsih (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The World Health Organization (WHO) reports that 75% of women have experienced vaginal discharge. If left untreated, vaginal discharge can lead to both psychological and physical health issues. In 2024, there were 318 reported cases of pathological vaginal discharge among women at Demang Sepulau Raya Hospital. One effective medium to increase the knowledge of women of reproductive age about vaginal discharge is the use of educational booklets. Purpos: to determine the effect of booklet-based on vaginal discharge knowledge among women of childbearing age Method: This quantitative study used a pre-experimental design, specifically a one-group pretest-posttest design. The population consisted of 130 women of childbearing age who sought treatment at the Obgyn Polyclinic of Demang Sepulau Raya Hospital. A total of 30 respondents were selected using purposive sampling. The study was conducted from February 2 to May 5, 2025. Data were collected using observation sheets and analyzed through univariate and bivariate analysis (paired sample t-test). Results: The results showed that the average knowledge score of women of reproductive age regarding vaginal discharge was 62.50 before the education and increased to 83.00 after the intervention. Conclusion: The analysis revealed a significant effect of booklet-based education on the knowledge of women of reproductive age at the Obgyn Polyclinic (p-value = 0.000). Suggestion: It is recommended that healthcare providers implement booklets as educational tools to enhance patients’ understanding of vaginal discharge and promote healthier behavior.